2018
DOI: 10.3892/mmr.2018.8924
|View full text |Cite
|
Sign up to set email alerts
|

Cell‑specific and roasting‑dependent regulation of the Keap1/Nrf2 pathway by coffee extracts

Abstract: Coffee is a popular beverage that contains various bioactive compounds. However, its molecular mechanism of action is not fully elucidated. In this context, two previously characterized coffee extracts, a lightly roasted and the corresponding green one, were investigated for their effect on nuclear factor erythroid 2-related factor 2 (Nrf2) target gene expression in myoblasts and endothelial cells using quantitative PCR. The tested concentrations were non-cytotoxic and led to improved redox cell status, as was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…The OO extracts were selected for further analysis in order to shed light on olive oils' mechanism of action. Based on the literature, polyphenols are able to cause Nrf2 detachment from the cytosol-localized Keap1 and subsequent translocation to the nucleus followed by antioxidant gene expression [30, 31]. The OO extracts were administered in HeLa cells at concentrations that caused the maximum increase in GSH levels and sequentially were assessed for their effect on gene expression levels of Nrf2 target genes by qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OO extracts were selected for further analysis in order to shed light on olive oils' mechanism of action. Based on the literature, polyphenols are able to cause Nrf2 detachment from the cytosol-localized Keap1 and subsequent translocation to the nucleus followed by antioxidant gene expression [30, 31]. The OO extracts were administered in HeLa cells at concentrations that caused the maximum increase in GSH levels and sequentially were assessed for their effect on gene expression levels of Nrf2 target genes by qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of all the aforementioned genes is subject to regulation by an antioxidant response element (ARE) in their promoter region, recognized by the Nrf2. These proteins are a part of the complex antioxidant machinery that protects cells from oxidative impairments by neutralizing ROS [31]. Therefore, extracts or compounds that upregulate their expression may be used as potential antioxidant supplements.…”
Section: Resultsmentioning
confidence: 99%
“…After exposure to several redox altering stimuli, highly reactive thiols of KEAP1 are subjected to instant modification, leading to NRF2 stabilization caused by its decreased affinity for the CUL3-KEAP1 complex. Subsequently, NRF2 translocates into the nucleus and binds to the antioxidant response element (ARE) located within the promoter region of specific target genes, inducing the expression of a large number of cytoprotective proteins with antioxidant and detoxifying roles [2][3][4][5]. The importance of NRF2 function has been demonstrated by several studies using NRF2-deficient mice showing an increased susceptibility to redox disturbances and xenobiotic stress [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The observed responses could be mainly attributed, at the molecular level, to specific transcription factors, namely, NF- κ B, p38 MAPK, members of the FoxO family, and nuclear factor erythroid-derived 2-like 2 (Nrf2) all activated by low ROS levels [ 38 , 39 ]. Focusing on Nrf2, it has been suggested that it is critical for the regulation of the intracellular redox status [ 40 , 41 ]. It acts by promoting both constitutive and inducible expressions of the antioxidant response element- (ARE-) regulated genes, which code for numerous antioxidant metabolites and enzymes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%